Unravelling The Threads: Aggression in the Tapestry of Parenting Styles - Sumbula Rahman (International Journal of Indian Psychȯlogy, 2024)
Many antecedents of violence are highlighted by the wealth of research on aggression in children and adolescents. Although scholars have noted the connection between aggressive behaviour in children and adolescents and parenting methods, there are not many studies that synthesize and organize the literature on the subject. The analysis demonstrates how parenting practices directly affect children’s hostility. While authoritarian and permissive parenting styles cause children to behave negatively and aggressively, authoritative parenting methods have a favourable impact on children’s psychological development. Additionally, the recent study indicates that there is potential for research on this subject in poorer nations. Future studies should be conducted in emerging and underdeveloped nations, with an emphasis on mixed methodologies, and look at the direct relationship between parenting styles and violent behaviour in children within various cultural contexts (include findings)